A novel peptide-enhanced drug delivery system for squamous cell oesophageal carcinoma - Adeyemi, Samson Adebowale (My University, 2017)
Cancer has been described as one of the major and leading causes of death worldwide. By the year 2030, it has been postulated that over 21.4 million new cases of cancer are anticipated, with 17 million cancer deaths annually and a total of 75 million people living with cancer within five years of diagnosis. Chemotherapy is the main therapeutic intervention for treating people living with oesophageal squamous cell carcinoma (OSCC). However, drug resistance, non-targeted delivery, sub-optimal dosage at disease sites and side effects on healthy cells have rendered it inefficient and ineffective in combating the disease even after combination chemotherapy. The paradigm shift in cancer nanomedicine employs the use of short functional peptides and ligands, conjugated to the surfaces of nanoparticles, for direct and active drug delivery systems in in vitro and in vivo assays. Smart and intelligent nanosystems remain a proactive and promising treatment alternative to circumvent the anomalies of current convectional cancer chemotherapeutics and enhance their delivery for optimal anti-tumoral effects. Based on these modalities, the conceptualization, design, optimization and characterization of a smart peptide-enhanced ligand-functionalized nano-construct – referred to herein as a PEL nanosystem – capable of encapsulating, targeting and controlling the release of endostatin (ENT), was fabricated in this study. Physicochemical parameters that characterized the design of a smart nano-construct in cancer therapy including satisfactory size, shape and surface properties, cellular uptake and internalization by tumor cells, low cellular toxicity to healthy cells and enhanced anti-tumoral activity of the encapsulated drug informed the fabrication of the PEL nanosystem. An optimized PEG-PEI-CHT nano-conjugate was developed as predicted by the Box–Behnken design model and surface-functionalized with Ly-P-1, PENT and FA as targeting moieties. Fourier Transform Infrared (FTIR) spectroscopy and Nuclear Magnetic Resonance (NMR) analysis confirmed the successful grafting of the nano-conjugates while Transmission Electron Microscopy (TEM) and Dynamic Light Scathering (DLS) analyses confirmed the synthesis of PEL nanoparticles with an average size less than 100nm. Scanning Electron Microscopy (SEM) results confirmed the morphology of the PEL nanosystem to be spherical with rough surfaces due to the attachments of the functionalized moieties. The release profile of the PEL nanosystem showed increased release of ENT at the acidic tumor micro-environment than observed at the physiological pH of healthy cells. Interestingly, the smart PEL nanosystem exhibited an enhanced targeted release of ENT for anti-tumoral effects on KYSE-30 cells relative to the unmodified nanosystem. The PEL nanosystem loaded with ENT showed a pragmatic inhibition of potent angiogenic factors including cell proliferation, nuclear apoptosis and necrosis, cell migration and invasion, as well as reduced expressions of both VEGF-C and MMP2 proteins as molecular makers for anti-angiogenesis. Athymic nude mice induced with OSSC xenografts showed a dramatic reduction in tumor volume with increased necrotic arears after treatment with the PEL ENT-loaded nanoparticles relative to the control. Overall, detailed in vitro, ex vivo cellular and in vivo experiments validated the fabricated PEL nanoparticulate systems as efficient delivery vehicles of ENT for enhancing its anti-tumoral activity by targeting the angiogenic pathway in KYSE-30 cells as presented in this study. While ENT was selected as a peptide-based anti-cancer model drug in this study due to its broad spectrum anti-angiogenic activities and limitations, the novel PEL nanosystem can be employed to incorporate alternative cancer chemotherapeutics for enhanced on-site delivery for an optimum therapeutic response in cancer therapy.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand in fulfilment of the requirements for the degree of Doctor of Philosophy. University of the Witwatersrand, Department of Pharmacy and Pharmacology, Johannesburg, South Africa. 2017.
Keywords: Esophagus--Cancer; Squamous cell carcinoma